The Effect of Job Involvement, Work Environment, and Career Development on Job Satisfaction - Burhanudin Burhanudin; Irwan Muhlisin; Mohamad Najmudin; I Ketut Mangku (Cita Konsultindo Research Center, 2023)
This study aims to examine the effect of job involvement on job satisfaction, examine the effect of the work environment on job satisfaction, and examine the effect of career development on job satisfaction. Respondents in this study were 120 employees at PT. Adi Satria Abadi. Data collection techniques were carried out using questionnaires, while data analysis used path analysis. The results showed that job involvement has a significant effect on job satisfaction, the work environment has an insignificant effect on job satisfaction, and career development has a significant effect on job satisfaction.